Sistem Kerja pada Mesin Winding Muratec Qpro Ex dalam Pembuatan Benang - Sukira Sukira; Didik Aribowo (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2025)
This study aims to determine the working system of the Qpro Ex Muratec Winding Machine at PT Budi Texindo Prakarsa. This study focuses on knowing the working system of the muratec Qpro EX winidng machine. As for what will be explained about the working system of the sorting and structuring winding machine, how the system works, and about the outside of the muratec qpro ex winding machine. In addition, it explains about special maintenance and control on the muratec qpro ex winding machine. The research method with the observation method where in this method makes direct observations to be able to find out the process of rolling yarn, literature studies sourced from references to journals, articles, books, and so on, the documentation method used by taking sample images of the observed machine parts.